Role of SAgs Produced by Staphylococcus aureus, rs893629 in TLR2 Gene in Progression of Recurrent Tonsillitis - AlChalabi, Rawaa; Mhawesh, Ahmed A.; AL-Tarboolee, Ahmed Yaseen; Wali, Mohammed H. (Iraqi Journal of Science, 2025)
Recurrent tonsillitis is characterized by five or more episodes of severe tonsillitis per year, which significantly impact daily life and normal activities. Superantigens (SAgs) trigger a massive response in T cells, resulting in an overwhelming release of cytokines and rapid T cell growth. Toll like receptor 2 (TLR2) is a substational pattern recognition receptor (PRR) for inflammation and the immune response. This study is designed to detect rs893629 in the TLR2 gene and genes encoding SAgs A, B and C in Staphylococcus aureus isolates. Additionally, the study examines the association between rs893629 and serum level of (TLR2, IFN-γ, MIF and IL-4) as a risk factor for the progression of tonsillitis. 261 patients, 89 healthy volunteers of both sexes, enrolled in this study. The tetra-arm PCR technique was used to detect rs893629, serum levels of TLR2 and cytokines were estimated with sandwich ELISA. Infections of tonsillitis were more common and severe in females than in males. Streptococcus pyogens represented the most common bacterial species98(49.2%),69 (34.7%) Staphylococcus aureus ,32(16.1 %) Haemophilus influenzae. S. aureus isolates from tonsillitis patients possesses one or more genes encoded the various types of SAgs, 69 (100%) of the isolates have SEA, 57 (82.6%) have SEB, and 48 (69.5%) contain SEC.  The genetic composition and allele frequencies of TLR2 rs893629 exhibited a significant difference between patient and control groups. The heterozygous genotypes GA was predominant among patients with an elevated frequency of allele G, while AA genotypes are dominant among healthy individuals. The results found notable variations between patients with recurrent tonsillitis and healthy controls in serum levels of TLR2, IFN-γ, MIF, and IL-4. In addition, the outcome found a highly significant difference in serum levels of TLR2 protein between patients who have a carrier GA genotype. Our findings indicate that the majority of S. aureus isolates produced more than one type of super antigen known as immunostimulatory toxins, that activate enormous numbers of T lymphocytes, significantly associate. The G allele of the TLR2 gene variant rs893629 is related with an increased risk of recurrent tonsillitis. The G allele is a risk factor that increases the chance of getting the sickness as well as its severity because of its positive link with the disease. High serum levels of TLR2, IFNγ, MIF, and low IL-4 levels are all regarded significant markers that may point to the severity of the illness.